PROVISIONS ON LINEAGE AND THE STATUS OF CHILDREN ACCORDING TO CLASSICAL SCHOLARS AND INDONESIAN POSITIVE LAW - Ihsan Siregar; Muhammad Amar Adly (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
This research investigates the fundamental differences regarding nasab (lineage) and child status under Islamic Law and Positive Law in Indonesia, along with their respective juridical consequences. A normative-juridical comparative methodology was employed, drawing on the Quran, Hadith, classical Fiqh texts, the Compilation of Islamic Law (KHI), Law No. 1 of 1974 on Marriage, and Constitutional Court Decision No. 46/PUU-VIII/2010. Findings reveal that Islamic Law rejects a lineage bond between a child born outside wedlock and the biological father; such a child’s nasab is exclusively tied to the mother and her family, excluding inheritance rights and marriage guardianship (wali nikah) from the paternal line. Indonesian Positive Law, following Constitutional Court Decision No. 46/PUU-VIII/2010, opens a legal avenue for out-of-wedlock children to establish civil ties with their biological father through scientific verification (DNA testing). Nonetheless, this ruling does not automatically alter nasab status regarding biological marriage guardianship under Islamic law. This legal convergence reflects the state’s commitment to safeguarding children’s c ivil rights without disregarding the sharia principles upheld in society.